If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x + 4y = 0 Solving 1x + 4y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 1x + 4y + -4y = 0 + -4y Combine like terms: 4y + -4y = 0 1x + 0 = 0 + -4y 1x = 0 + -4y Remove the zero: 1x = -4y Divide each side by '1'. x = -4y Simplifying x = -4y
| 30y^2-82y-24=0 | | 3(5p-3)=5(p-2) | | -5+8y-4y=0 | | 6=n-(-14) | | f(n)=8+3(n-1) | | -11=25x+13-x | | 0.5k+0.17=0.42 | | 8x^5-192x^4+1536x^2=0 | | 19x-45-9x=5 | | x^2-5mx+6m^2+m-1=0 | | x^3-24x^2+192=0 | | 53=17x-10-8x-9 | | 8+x+9=8+x+9 | | Y+2(-1)=0 | | 10r-84=4 | | 6X+15-5(X+7)+30=12 | | 6x-5=6(x-1)+14 | | 10-43=2x+21 | | (9x+18)=54 | | 6y+5x=28 | | x^7=2.5 | | 3x-6=-2x+11 | | x^5-2x^4-x-3=0 | | 2c+4x=23 | | Y-3(-1)=4 | | Y-3(-2)=4 | | 3.0+3.0x=3.2 | | 4-x=[2-3x] | | 7-.625x=-2 | | .75x=180 | | 4(0)+2y=6 | | 100=10(logI-logI[0]) |